KONTRIBUSI SUKUK KORPORASI TERHADAP PRODUK DOMESTIK BRUTO (PDB) INDONESIA TAHUN 2017-2021 - Irma Nur Hidayah (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2023)
This research aims to explore the impact of sukuk on economic growth, particularly in the context of the Gross Domestic Product (GDP) in Indonesia. The research method used is a qualitative approach through literature review. The findings of this study conclude that investment in corporate sukuk contributes to the growth of Indonesia's GDP, although descriptively the value of circulating corporate sukuk only contributes a small fraction of the total GDP, which is below half a percent. Sukuk influences economic growth through GDP by providing funding obtained from the issuance of corporate sukuk..